Kant's Intuitionism : A Commentary on the Transcendental Aesthetic - Falkenstein, Lorne (Book collections on Project MUSE., 1995)
"Ever since the publication of his Critique of Pure Reason in 1781, Immanuel Kant has occupied a central position in the philosop Transcendental Aesthetic, namely, his position on how we manage to intuit the properties and relations of objects as they exist in space and time." "It is a major problem not only in philosophy, but in cognitive science in general, to decide how much structure sensory input has of itself and how much we give it through processing. How much do our faculties do to structure our knowledge of objects and to give them their spatial and temporal existence? Recent interpretations of Kant's doctrine of intuition have emphasized the constructivist answer to this question, stressing that sensations have no structure of their own and that, for the objects of our experience to have any spatial or temporal structure at all, we must impose a structure through synthetic processes of the imagination or understanding. Rehabilitating an interpretation of Kant outlined in the nineteenth century, Falkenstein argues that our knowledge of objects in space and time is not grounded in concepts but in the quasi-physiological constitution of our senses." "Falkenstein begins with a careful critique of both historical and contemporary approaches to this problem and goes on the develop a cogent and stimulating argument for his position. The dialectic that results advances the discussion into controversial new realms, revitalizing the debate about the implications of Kant's Transcendental Aesthetic."--Jacket